Pollination efficiency and foraging behaviour of honey bees and non‐Apis bees to sweet cherry. (20th November 2019) - Eeraerts, Maxime; Vanderhaegen, Ruben; Smagghe, Guy; Meeus, Ivan
Abstract: Crop pollination generally increases with pollinator diversity and wild pollinator visitation. To optimize crop pollination, it is necessary to investigate the pollination contribution of different pollinator species. In the present study, we examined this contribution of honey bees and non‐ Apis bees (bumble bees, mason bees and other solitary bees) in sweet cherry. We assessed the pollination efficiency (fruit set of flowers receiving only one visit) and foraging behaviour (flower visitation rate, probability of tree change, probability of row change and contact with the stigma) of honey bees and different types of non‐ Apis bees. Single visit pollination efficiency on sweet cherry was higher for both mason bees and solitary bees compared with bumble bees and honey bees. The different measures of foraging behaviour were variable among non‐ Apis bees and honey bees. Adding to their high single visit efficiency, mason bees also visited significantly more flower per minute, and they had a high probability of tree change and a high probability to contact the stigma. The results of the present study highlight the higher pollination performance of solitary bees and especially mason bees compared with bumble bees and honey bees. Management to support species with high pollination efficiency and effective foraging behaviour will promote crop pollination.